2018
DOI: 10.1177/0954406218774378
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of multi-pass turning and multi-pass face milling using subpopulation firefly algorithm

Abstract: In this paper, Subpopulation Firefly Algorithm is proposed for optimization of machining parameters in multi-pass turning and multi-pass face milling operations. Basic Firefly Algorithm is modified with the aim to avoid space of local minimum and to meet the operation constraints in each iteration step. For that purpose, the following modifications are made: one firefly population is divided into two, a crossover operator is introduced and the searching for new design variables is continued until constraint fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Regression analysis was used. As regards solving the mathematical models of machining parameters optimisation, literature supplies a series of models [3][4][5][6][7][8][9][10][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Regression analysis was used. As regards solving the mathematical models of machining parameters optimisation, literature supplies a series of models [3][4][5][6][7][8][9][10][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The optimization is made for the lowest surface roughness and cutting temperature and there are used two methods: teaching-learning-based optimization and bacterial foraging optimization. Miodragovic et al [33] propose the use of a subpopulation firefly algorithm (SP-FA) for the optimization of multi-pass turning. The objective function refers to minimizing unit production costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many methods are based on the mathematical models overtaken from Shin and Joo [6], Gupta et al [8], Chen and Tsai [9], Chen [11], Mellal and Williams [26]. There are also presented certain comparative results [14,15,20,25,[27][28][29]33,35]. From the searched literature it results that machining parameters optimization can be done in three modalities: (a) into two separate phases, one for the roughing machining and the second for the finishing machining; (b) global approach, into a single phase; (c) pass optimization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The optimal values of speed, feed and depth of cut in each pass were determined for minimum total production cost. Miodragović et al [17] endeavored to modify the basic FA technique to optimize different machining parameters in multi-pass turning and multi-pass face milling operations subject to various practical operational constraints. It was concluded that the proposed algorithm had the ability to reach the global optimal solutions for complex optimization problems.…”
Section: Literature Surveymentioning
confidence: 99%
“…multiple roughing passes and a single finishing pass. For roughing operation, length of tool (cutter) path (L r ) can be expressed as [17]:…”
Section: Mathematical Model For Multi-pass Face Milling Operationmentioning
confidence: 99%